Analysis of stakeholders in Mesoamerica for adaptation of agriculture to climate change - Baena, M. (Bioversity International, 2013)
This document describes a process to identify stakeholders in Mesoamerica for work related to adaptation of agriculture to climate change, and select particularly those who could be boundary partners in current or future projects.